Decreased tissue oxygenation in newborns with congenital heart defects: a case-control study - Fister, Petja (Croat Med J, 2018)
AIM: To compare regional tissue oxygenation (rSO(2)) in the brain, intestine, and kidney between newborns with and without congenital heart defects (CHD). METHODS: This observational case-control study was conducted at the Neonatal Deparetment of Children's Hospital Ljubljana between December 2012 and April 2014. It included 35 newborns with CHD and 30 healthy age- and sex-matched controls. CHD were assessed echocardiographically and divided into acyanotic and cyanotic group. RSO(2) in the brain, intestine, and kidney was measured using near-infrared spectroscopy (NIRS). Simultaneously, heart rate (HR), breathing frequency (BF), mean arterial blood pressure (MAP), and arterial oxygen saturation (Sao(2)) were recorded. RESULTS: Newborns with CHD had significantly lower rSO(2) in the left brain hemisphere (67 ± 11% vs 76 ± 8%, P = 0.004), right brain hemisphere (68 ± 11% vs 77 ± 8%, P < 0.001), and the kidney (68 ± 13% vs 77 ± 10%, P = 0.015). RSO(2) in the intestine did not significantly differ between the groups. HR, MAP, and Sao(2) also did not differ between the groups, whereas BF was significantly higher in the CHD group (57 ± 12 vs 39 ± 10 breaths/min, P < 0.001). Between cyanotic and acyanotic group, we found no significant differences in rSO(2) of any tissue. CONCLUSIONS: Monitoring tissue oxygenation by NIRS could enable a timely detection of hemodynamically important CHD.